Coffee in Indian Economy: Performance and Prospects - Thrilok Belli B M; Veershetty; Jagadeesh M S; Neelakantappa P; Prashant; Abhishek G J. (Archives of Current Research International, 2024)
Coffee is a universal hot beverage, and its international trade volumes point to significant approval in favour of coffee consumption. For many nations in the tropics, coffee is a major source of foreign exchange. This study provides a comprehensive analysis of the global and domestic coffee industry, with a particular focus on India’s role based on the secondary data taken from different sources like ITC trade map, Coffee Board of India and international coffee organization statistics, etc. In 2022, global coffee production reached 10.89 million tons, with Brazil, Vietnam, and Indonesia leading the output. Despite being the eighth-largest coffee producer, India’s export ranking is relatively low due to significant domestic consumption. This study employs standard econometric tools, such as compound annual growth rate, Cuddy Della Index, Markov chain analysis, etc. The Johansen co-integration test revealed a long-run equilibrium relationship among selected Arabica and Robusta coffee markets. Furthermore, the pair-wise Granger causality test identified unidirectional causality in price transmission among certain Arabica markets, while bidirectional causality was observed among Robusta markets. The paper also highlights the declining coffee yield in India due to biotic and abiotic stressors, despite an increase in production and cultivation area. The study concludes with a discussion on the dynamics of Indian coffee exports, where high domestic demand and fluctuating international prices contribute to the sector’s variability. This research provides valuable insights into the performance and prospects of the coffee industry within the Indian economy, offering a basis for future policy and market interventions.